OP0067 Dickkopf-1 (DKK1) serum levels and bone quality (tbs evaluation) in patients with systemic sclerosis and rheumatoid arthritis. (12th June 2018) - Casabella, A.; Ruaro, B.; Paolino, S.; Pizzorni, C.; Alessandri, E.; Seriolo, C.; Fasciolo, D.; Botticella, G.; Molfetta, L.; Odetti, P.; Seriolo, B.; Cutolo, M.
Abstract : Background: Systemic sclerosis (SSc) as well as rheumatoid artrhritis (RA) patients present an increased risk of osteoporosis (OP) as a result of the chronic inflammatory state, low vitamin D, immobilisation and other causes. The Wnt/β-catenin pathway is signalling identified like a key promoters of the osteoblastogenesis hence of the new bone formation in inflammatory conditions. Dickkopf-1 (DKK1) is a natural inhibitor of Wnt signalling pathway that could be involved in promoting osteoclastogenesis through suppression of osteoprotegerin. 1 Trabecular Bone Score (TBS) is an index of bone quality extracted from dual-energy X-ray absorptiometry (DXA) analysis. 2 Objectives: In this study, bone mineral density (BMD) and Dkk-1 levels were evaluated in SSc patients, in order to investigate possible associations between systemic OP and/or osteopenia and Dkk-1 concentrations, according to their different nailfold videocapillaroscopic (NVC) patterns of microangiopathy (NVC patterns 'Early', 'Active', and 'Late') 3 in SSc patients and to compare the results regarding bone quality with RA patients and healthy subjects (CNT). Methods: Eighty-four SSc patients, 98 rheumatoid arthritis (RA) and 60 CNT were studied. Dkk-1 serum levels were measured by ELISA methods (Quantikine Human DKK-1 Immunoassay R and D System, Minneapolis, USA). Bone Mineral Density (BMD, g/cm 2 ) of the lumbar spine (L1-L4) was analysed by dual-energy X-ray absorptiometry (DXA) scan. Lumbar spine bone quality was derived from each spine DXA examination using the TBS analysis. Nailfold videocapillaroscopic (NVC) patterns were analysed as previous reported. 3 25 hydroxyvitamin D (25(OH)D ng/ml) serum concentration was evaluated in all subjects. Results: Serum DKK-1 levels were significantly higher in patients with SSc than in CNT (2892±1121 pg/ml vs 2044±692 pg/ml, p<0.007). Dkk-1 levels were statistically significantly higher in patients with 'Late' SSc pattern than in those both 'Active' and 'Early' pattern (3467±954.1 pg/ml, 2290±487.8 pg/ml, 1827±888.3 pg/ml respectively, p<0.0001). A negative correlation between Raynaud's phenomenon duration (years expressed) (p<0.01) and Dkk-1 levels (p<0.001) was also observed).TBS values were found statistically higher in SSc with a 'Early' NVC pattern, compared to the 'Active' or 'Late' pattern, (p<0.001). Only in the 'Late' NVC pattern group a significant negative correlation was observed between TBS and Dkk-1 values (p<0.001). No statistical significant difference was observed in the three groups about DXA values (p=0.13, for all areas). Serum levels of 25 (OH) D were statistically significantly higher in patients with 'Early' SSc pattern than in those both 'Active' and 'Late' NVC pattern (19.1±7.5, 15.1±5.3, 12.1±7.1 respectively, p=0.002). Conclusions: The data obtained showed a significantly Increased of Dkk-1 serum concentrations together and a decreased bone mass (lower TBS and BMD) in SSc patients compared to CNT. The bone quality seems lower in SSc patients with more altered microvasculature ('Late' NVC pattern). References: [1] Krishnan V, et al. J Clin Invest2006;116:1202–9. [2] Roux JP, et al. Osteoporosis Int 2013;24:2455–60. [3] Cutolo M, et al. J Rheumatol2000;27:155–60. Disclosure of Interest: None declared